Effects of Habitat Differences and Invasive Species Competition on Age and Growth of Triplophysa strauchii - Ya-Han Meng; Wei-Zhen Gao; Yan Li; Lei Shi (Animals, 2025)
Accurate age determination is fundamental for investigating fish population dynamics and growth patterns. This study used the lapillus to determine age in Triplophysa strauchii populations from an oxbow lake and a stream. Growth patterns were evaluated using three models (the Von Bertalanffy, Gompertz, and Logistic models). The oxbow lake population showed faster growth and longer lifespan (6 years in Dacao Lake; 5 years in Liutiao Stream). Conversely, the stream population displayed a trend toward smaller size and younger age. Both populations exhibited higher Fulton’s condition factor in juveniles than in adults. The species exhibited a fast-growth type, with similar fitting results across models. These findings reflect subtle differentiation in life history strategies across habitats, likely related to environmental conditions and competitive pressure from invasive species. These insights into T. strauchii life history underscore the importance of further research to support conservation and sustainable management of this endemic species.